Identité enseignante et collège inclusif : quels remaniements face à un environnement de travail en mutation ? - Benoit Piroux (Recherches en Éducation)
The 2005-102 law, called “law for chances equality, participation and citizenship for handicapped people”, permitted to show obvious links between the universe of specialized education and the ordinary school system. This political will, coupled with a social evolution towards postmodernism, induced a deep mutation concerning the role of high school teachers, who are nowadays situated between, one of the hand their institution, hardly understandable because of the masses of daily directives, and on the other hand, their more and more heterogeneous “daily users”. Beyond a support on personal experience and abilities, we notice a game of positioning in a new space of expression, in order to respond to a need for identity coherence, combining aspirations, representations of a vocation, regard to significant others and request from the institution.